Canada’s Invisible Nationality Policy: Creating Ethnicity, Managing Populations, Imagining a Nation - Efremkin, Evgeny (Journal of the Canadian Historical Association / Revue de la Société historique du Canada, 2013)
This article explores the process of national identity construction at Canadian borders in the 1930s. Based on the examination of customs declaration forms (transatlantic ship manifests) of arriving passengers at the port of Quebec in the first half of the 1930s, as well as Royal Canadian Mountain Police (RCMP) files, I suggest that the Canadian bureaucracy, informed by social Darwinist views of race and ethnicity, and the Anglophone bourgeois concern over modernization brought upon by the forces of industrialization and urbanization, developed an elaborate system of categorization of Canada’s population according to prescribed criteria of ethnicity, nationality, and race. Utilizing critical discourse analysis, I argue that in efforts to “know” and control its growing population, the Canadian state developed a rigid, albeit an invisible nationality policy. Although there was never an official nationality policy in place in Canada in the 1930s, public officials, the media, and security agencies not only operated with an acute awareness of national and ethno-racial differences in the society, but also worked to reinforce such divisions in attempts to maintain the social order and the cultural, social, and economic status quo. In this work, I imply that border officials were directly responsible for constructing specific representations of Canada’s ethnic populations, all within the context of an impending need to control the population of a rapidly modernizing society, where the Canadian community had to be made “knowable,” familiar, and recognizable in the official discourse.